Relationship of emotional intelligence and academic performance among University of the Philippines Manila College of Dentistry Students - Abucejo, Joanna Lucille S.; Tagum, Leah L.; Alfaro, Arlene Cecilia A. (Adviser).
INTRODUCTION: Emotional Intelligence (EI) was defined by Salovey and Mayer as the ?ability to monitor one's own and others' feelings and emotions, to discriminate among them and to use this information to guide one's thinking and actions? (Salovey, Brackett, Mayer, 2004). Many studies have correlated EI with Academic Performance and one of these is by Farooq in 2003 which says that the achievement of good academic results is contributed not only by higher intelligence but by EI as well.
METHODS: In phase I, the correlation between EI and Academic Performance among UPCD Students were determined. Students from 1st to 3rd year dentistry proper were asked to answer the Schutte Self-Report Emotional Intelligence Test (SSEIT). With their consent, GWAs were accessed and the correlation was done. For Phase 2, a focus group discussion was conducted.
RESULTS: Those who have higher EI have lower academic performance. EI and GWA were also correlated with other variables and among these only age appeared to be statistically significant when correlated with academic performance. On the other hand, only tuition fee bracket appeared to be statistically when correlated with EI. For phase 2, the identified stressors are the following: many and frequent examinations, full academic load in some semesters, laboratory requirements, negative approach of some of the professors, the physical environment and bullying.
CONCLUSION: The EI of UPCD students are generally high. EI of the UPCD students have a positive yet weak correlation to their GWAs. As identified in the Focus Group Discussion, stimuli that are perceived as stress is very evident in the college.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Academic achievement; Dentistry; Emotional Intelligence; Academic performance; Stressor; Coping mechanisms